Pandemic covid-19 as a catalyst of the global logistic crisis and digitalization systems - Binda, Jacek; Bolibrukh, Lidia (Scientific Journal of Bielsko-Biala School of Finance and Law, 2022)
The logistics industry is developing rapidly at the global level. The trend toward implementing virtual reality in business and digitalization is growing. The growth of consumer demand for logistics services and their high quality provokes an increase in freight turnover around the world, allowing logistics processes to improve. At the same time, the beginning of the COVID-19 pandemic was an unpredictable event that led to a crisis and chaos in logistics and demonstrated the unpreparedness of global logistics for such situations. Researchers say the effects of the pandemic are just beginning and will last for the next three years.The study aims to determine the duration of the effects of a pandemic, their impact on logistics, and identify the preconditions for preventing potential crises. To achieve this goal, it is necessary to analyze the effect of the COVID-19 pandemic on global logistics, predict the development of the logistics crisis for the next study period, conclude, and offer recommendations.Logistics was able to respond quickly to the new challenge of the COVID-19 pandemic and adapt to the new realities of doing business. However, together with such a phenomenally rapid change in the accepted order of life and adjustment to the remote "new" normality, humanity struggles with new waves of the pandemic.